2021
DOI: 10.1016/j.conctc.2021.100770
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of response to Certolizumab-Pegol in rheumatoid arthritis (PreCePRA) by functional MRI of the brain – Study protocol for a randomized double-blind controlled study

Abstract: Background Tumor necrosis factor inhibitors (TNFi) signify a major advance in the treatment of rheumatoid arthritis (RA). However, treatment success initially remains uncertain as approximately half of the patients do not respond adequately to TNFi. Thus, an unmet need exists to better predict therapeutic outcome of biologicals. Objectives We investigated whether brain activity associated with arthritis measured by functional magnetic resonance imaging (fMRI) of the bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…We screened 1149 records identified by the search and found 11 eligible studies (eFigure 1 in Supplement 1). Among them, we could not access the individual-level data for 6 studies . Hence, we included 5 studies for analysis: RAPID (Rheumatoid Arthritis Prevention of Structural Damage) 1, RAPID 2, REALISTIC (Certolizumab Pegol for the Treatment of Patients With Active Rheumatoid Arthritis), Choy et al, and C-EARLY (Multi-center, Randomized, Double-blind, Placebo-controlled Study to Evaluate the Efficacy and Safety of Certolizumab Pegol in Combination With Methotrexate in the Treatment of Disease Modifying Antirheumatic Drugs–Naive Adults With Early Active Rheumatoid Arthritis) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We screened 1149 records identified by the search and found 11 eligible studies (eFigure 1 in Supplement 1). Among them, we could not access the individual-level data for 6 studies . Hence, we included 5 studies for analysis: RAPID (Rheumatoid Arthritis Prevention of Structural Damage) 1, RAPID 2, REALISTIC (Certolizumab Pegol for the Treatment of Patients With Active Rheumatoid Arthritis), Choy et al, and C-EARLY (Multi-center, Randomized, Double-blind, Placebo-controlled Study to Evaluate the Efficacy and Safety of Certolizumab Pegol in Combination With Methotrexate in the Treatment of Disease Modifying Antirheumatic Drugs–Naive Adults With Early Active Rheumatoid Arthritis) .…”
Section: Resultsmentioning
confidence: 99%
“…Patients in 4 studies tended to have longer disease duration compared with the other study. eTable 1 in Supplement 1 presents available characteristics of the 6 eligible studies without available IPD . One study had no results published, and 4 studies were conducted in Asian countries under similar settings with the RAPID trials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 One group is analyzing whether functional brain magnetic resonance imaging could predict the response to the TNF inhibitor, certolizumab, in patients with rheumatoid arthritis. 7 Others have suggested that machine learning could be used to optimize the benefit from TNF inhibitors. 8 Clearly, biomarkers would be valuable in these pursuits.…”
mentioning
confidence: 99%